Experimental tests and numerical modeling of ballistic impact on honeycomb sandwich structures reinforced by functionally graded plates. (December 2017) - Arslan, Kemal; Gunes, Recep; Apalak, M Kemal; Reddy, JN
The aim of this study is to determine the ballistic impact response of a novel sandwich structure consisting of aluminum honeycomb and Al/SiC functionally graded face sheets and develop a compatible numerical model with experiments. The experiments were carried out by a single-stage gas gun system and numerical simulations were performed using the explicit finite element code, LS-DYNA®. The mechanical properties of the functionally graded face sheets through the thickness were considered in accordance with a power-law distribution. The Mori–Tanaka scheme was used in order to determine the effective material properties of the functionally graded face sheets at a local point. In order to simulate the elastoplastic behavior of the functionally graded face sheets, Tamura–Tomota–Ozawa model was implemented in the numerical model. The ballistic performance of the sandwich structure was investigated for metal-rich ( n = 0.1), linear ( n = 1.0), and ceramic-rich ( n = 10.0) compositions of the functionally graded face sheets. The results indicated that the ceramic fraction of the functionally graded face sheets was quite influential on energy absorption capability, damage mechanism, and impact resistance of the sandwich structure. The sandwich structure with linear functionally graded face sheets showed the highest ballistic performance in terms of damage and deformation shapes of the entire sandwich structure among investigated material compositions.